2021
DOI: 10.1186/s12891-021-04123-w
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan polysulfate sodium for Ross River virus-induced arthralgia: a phase 2a, randomized, double-blind, placebo-controlled study

Abstract: Background Alphaviruses, such as Ross River (RRV) and chikungunya virus (CHIKV), cause significant global morbidity, with outbreaks of crippling joint inflammation and pain, leaving patients incapacitated for months to years. With no available vaccine or specific therapeutic for any alphaviral disease, and a growing economic and public health burden, there is a serious need for the development of specific therapies. Methods This study evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It is possible that low grade chronic inflammation remains [ 9 ]. In the absence of vaccine, antivirals or targeted therapeutic solutions, RRV disease is generally treated with non-steroidal anti-inflammatory drugs (NSAIDs) or analgesics such as paracetamol, and recent clinical trials have shown some efficacy of pentosan polysulfate sodium (PPS), a sulphated polysaccharide, which is available as a prescription in Australia [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that low grade chronic inflammation remains [ 9 ]. In the absence of vaccine, antivirals or targeted therapeutic solutions, RRV disease is generally treated with non-steroidal anti-inflammatory drugs (NSAIDs) or analgesics such as paracetamol, and recent clinical trials have shown some efficacy of pentosan polysulfate sodium (PPS), a sulphated polysaccharide, which is available as a prescription in Australia [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We have recently reported that PPS is able to improve hand strength in patients suffering from RRV [ 15 ]. By using a well characterised adult mouse model of CHIKV infection [ 16 ], we assessed if PPS treatment could treat the functional signs of CHIKV disease by improving grip strength.…”
Section: Resultsmentioning
confidence: 99%
“…PPS is a repurposed semisynthetic glycosaminoglycan that has been shown to be well-tolerated in both oral and injectable forms. Recently, injectable PPS (iPPS) was administered to a cohort of RRV infected patients with no serious adverse events reported [ 15 ]. We have demonstrated that CHIKV-infected untreated mice develop the classical rheumatic features of local inflammation as observed by foot and joint swelling and histological evidence of arthritis as seen by cellular infiltrates, tenosynovitis and myositis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although pentosan polysulfate treatment did not influence the kinetics of virus infection, it alleviated virus-induced arthritis in C57BL/6 mice [ 139 ]. Furthermore, it was recently successfully evaluated in phase II clinical trials for the treatment of RRV-induced arthritic disease (PARA_004, Paradigm BioPharmaceuticals) [ 210 ]. Pixatimod treatment also reduced the severity of alphavirus-induced arthritis and showed good antiviral effects against different CHIKV strains [ 140 ].…”
Section: Targeting Host Factorsmentioning
confidence: 99%